2015
DOI: 10.1021/acs.jpcc.5b03407
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous (Glassy) Carbon, a Promising Material for Sodium Ion Battery Anodes: a Combined First-Principles and Experimental Study

Abstract: We present a comparative, combined ab initio and experimental study of sodium and lithium storage in amorphous (glassy) carbon (a-C) vs. graphite. Amorphous structures are obtained by fitting stochastically generated structures to a reference radial distribution function.Li insertion is thermodynamically favored in both graphite and a-C. While sodium insertion is thermodynamically unfavored in graphite, a-C possesses multiple insertion sites with binding energies stronger than Na cohesive energy, making it usa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 46 publications
3
58
0
Order By: Relevance
“…For Li, this meant increased voltages. Computed voltage-capacity curves for lithiation and sodiation agreed well with experimentally measured curves using thoroughly amorphized carbon [25]. Our calculations also showed a significant magnitude of strengthening of insertion energy of Mg and K by amorphization [27], as is also shown in Figure 3, implying the possibility of electrochemical activity after amorphization.…”
Section: Insertion Of LI Na K and Mg In Carbon: Effects Due To Ionsupporting
confidence: 84%
See 2 more Smart Citations
“…For Li, this meant increased voltages. Computed voltage-capacity curves for lithiation and sodiation agreed well with experimentally measured curves using thoroughly amorphized carbon [25]. Our calculations also showed a significant magnitude of strengthening of insertion energy of Mg and K by amorphization [27], as is also shown in Figure 3, implying the possibility of electrochemical activity after amorphization.…”
Section: Insertion Of LI Na K and Mg In Carbon: Effects Due To Ionsupporting
confidence: 84%
“…Here, we only introduce key computed quantities which are important for a material's performance as an active electrode material and which are discussed in Sections 2 and 3. To analyze the thermodynamics of interaction of a potential electrode material with Li, Na, K, Mg, or Al, we use the binding energy E b (n) of n of these atoms to the active material, which is effectively the defect formation energy (E f , which is the term used in many studies [11][12][13]15,16,[19][20][21][22][23][24][25]). It is computed as:…”
Section: Key Computed Quantitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such increase in ionicity might originate from vanadium reduction to V(III) in addition to local vanadium-oxygen coordination changes, i.e. further amorphisation [5, 2729]. Overall charge-discharge features of a-VOx-6 Pa are similar to other a-VOx materials synthesised by different routes in other works as referred in the present work.…”
Section: Resultssupporting
confidence: 64%
“…[ 138,269, The storage of Na in carbon materials such as hard carbon, amorphous carbon, defected graphene, and functionalized graphite has been observed to be thermodynamically feasible. [ 325,326,274,276 ] In the early works by Doeff et al, they demonstrated that the extent of Na intercalation in carbon materials varies depending on the carbon structure; NaC 70 , NaC 30 , and NaC 15 were formed for graphite, petroleum coke, and Shawinigan black, respectively. [ 277 ] The inserted Na ions were also reversibly extracted from the carbon materials.…”
Section: Non-graphitic Carbonmentioning
confidence: 99%